Special issue on alternative reality and analytics for learning: (2017)
One of the main challenges in modern education is to blend formal official learning with a huge variety of content provision, group discussion, self-entrepreneurship, user’s own portfolio, and long lists of possibilities off-the-classroom. Informal learning happens anytime, anywhere. We strongly believe that formal learning does too. The cornerstone is to find the right balance between both contexts. The effective integration of Open Educational Resources with formal lessons, or between traditional lectures and live multi-user conferences, or even more, between spontaneous forum contributions outside the learning management system, and the  official activities towards certification, will make  the difference: the actual change of an educational paradigm. And this could be so for every single shareholder of the educational community, from teachers to tutors, from support staff to managers, from content providers to learning designers and, of course, from students to graduates.